Indicators of Food Activity As Breeding Dairy Cattle Characteristics - Sedunova, Tatyana; Kudrin, Alexander; Mechanikova, Marina; Smirnova, Julia (KnE Life Sciences, 2019)
The article presents the data of ethological studies on dairy cows of the Ayrshire breed of the second lactation under conditions of stall-tethered keeping in the spring. Animals with increased nutritional activity have milk yield per 305 days of lactation higher by 1662 kg (P> 0.999) compared with animals with reduced nutritional activity. The amount of milk fat in animals with increased food activity is 72.8 kg more (P> 0.999), and the total amount of milk protein is 47.8 kg more (P> 0.999) than in animals with reduced food activity. An increased index of food activity characterizes Ayrshire cows. Comparison of milk yields obtained from Ayrshire cows with milk yields of cows with reduced food activity leads to the establishment of the following results: there is a difference in milk yield for the first lactation of 1179 kg (P> 0.999), a difference in the amount of milk fat 53.2 kg (P> 0.99), and by the amount of milk protein – 36.4 kg (P> 0.99). Comparison of the total activity index led to the following results: the difference in milk yield per 305 days of lactation is 1386 kg (P> 0.999), in the amount of milk fat 61.3 kg (P> 0.999), milk protein 40.0 kg (P> 0.999). The highest correlation is observed between the index of food activity and milk productivity in ultra-active animals. In infra-passive cows, the correlation between the index of food activity and milk productivity is negative. Therefore, an effective means of increasing milk productivity is the selection of animals of Ayrshire breed by ethological individuality, taking into account indices of food, motor, and general activity. The studied indices of ethological activity are inherited by cows and can be effectively used in breeding and breeding with highly productive cattle of the Vologda selection.